CO2 SOLUBILITY AND SPECIATION IN INTERMEDIATE (ANDESITIC) MELTS: THE ROLE OF H2O AND COMPOSITION - King P.L.; Holloway J.R. (My University, 2002)
We determined total CO2 solubilities in andesite melts with a range of compositions. Melts were equilibrated with excess C-O(-H) fluid at 1 GPa and 1300°C then quenched to glasses. Samples were analyzed using an electron microprobe for major elements, ion microprobe for C-O-H volatiles, and Fourier transform infrared spectroscopy for molecular H2O, OH-, molecular CO2, and CO32-. CO2 solubility was determined in hydrous andesite glasses and we found that H2O content has a strong influence on C-O speciation and total CO2 solubility. In anhydrous andesite melts with ~60 wt.% SiO2, total CO2 solubility is ~0.3 wt.% at 1300°C and 1 GPa and total CO2 solubility increases by about 0.06 wt.% per wt.% of total H2O. As total H2O increases from ~0 to ~3.4 wt.%, molecular CO2 decreases (from 0.07 +/- 0.01 wt.% to ~0.01 wt.%) and CO32- increases (from 0.24 +/- 0.04 wt.% to 0.57 +/- 0.09 wt.%). Molecular CO2 increases as the calculated mole fraction of CO2 in the fluid increases, showing Henrian behavior. In contrast, CO32- decreases as the calculated mole fraction of CO2 in the fluid increases, indicating that CO32- solubility is strongly dependent on the availability of reactive oxygens in the melt. These findings have implications for CO2 degassing. If substantial H2O is present, total CO2 solubility is higher and CO2 will degas at relatively shallow levels compared to a drier melt. Total CO2 solubility was also examined in andesitic glasses with additional Ca, K, or Mg and low H2O contents (<1 wt.%). we found that total co2 solubility is negatively correlated with (Si + Al) cation mole fraction and positively correlated with cations with large Gibbs free energy of decarbonation or high charge-to-radius ratios (e.g., Ca). Combining our andesite data with data from the literature, we find that molecular CO2 is more abundant in highly polymerized melts with high ionic porosities (>~48.3%), and low nonbridging oxygen/tetrahedral oxygen (<~0.3). Carbonate dominates most silicate melts and is most abundant in depolymerized melts with low ionic porosities, high nonbridging oxygen/tetrahedral oxygen (>~0.3), and abundant cations with large Gibbs free energy of decarbonation or high charge-to-radius ratio. In natural silicate melt, the oxygens in the carbonate are likely associated with tetrahedral and network-modifying cations (including Ca, H, or H-bonds) or a combinations of those cations.